Perlindungan Hukum terhadap Investor Pada Aplikasi Investasi Saham Berbasis Online - Andreas Hasintongan Simanjuntak (Syntax Corporation Indonesia, 2023)
The development of information technology has had a significant impact on the world of investment, with the emergence of online-based stock investment applications. Along with its popularity, legal protection of investors has become very important. This study aims to analyze and evaluate the legal protection mechanism provided to investors on online-based stock investment applications. The method applied in this legal research is the study of normative juridical research methods, which refers to research on substance analysis of laws and regulations, books, journals and papers as well as other jurisprudence. Normative research because research specifications are more made on secondary instructions in the library. The results showed that legal protection for investors in online stock investment applications involves various aspects, ranging from laws and regulations to internal policies of application organizers. Existing regulations, both national and international, provide a legal basis that protects the rights of investors, but there are still some weaknesses in their implementation. Legal uncertainty, information transparency, and the responsibility of application operators are crucial aspects that need to be improved to improve investor protection. Regulatory alignment, the active role of supervisory authorities, and education to investors are also key steps in improving legal protection for investors on online-based stock investment applications.